Overexpression of TRPM2 Channels by Oxidative Stress- Mediated Reperfusion Injury - Balgetir, Ferhat; Kuloğlu, Tuncay; Bulut, Serpil; Demir, Caner Feyzi; Balgetir, Merve Kavak; Gönen, Murat; Aytac, Emrah (My University, 2022)
Objective: Since it can be activated by oxidative stress, the TRP melastatin 2 (TRPM2) channel\rhas recently been established as a potential therapeutic target in the fight against oxidative stress-\rrelated diseases including diabetes, inflammation, myocardial infarction. The main objective of this\rstudy was to investigate the expression of TRPM2 cation channel and histopathological effects in\rrat cerebral ischemia-reperfusion model.\rMaterials and Methods: A total of 30 adult male Wistar-Albino rats were used in the study. The\ranimals were divided into 5 groups. In the sham groups bilateral common carotid arteries were\runcovered and the rats were decapitated at the 2nd and 6th hours of the experiment. In the\rischemia/reperfusion (I/R) groups (I/R-2 and I/R-6), bilateral common carotid arteries were\runcovered then were clamped using aneurysm clips for 45 min and reperfusion was induced for 2\rand 6 hours, respectively. At the end of the experiment malondialdehyde (MDA) and TRPM2\rmRNA levels were measured. The tissues were fixed in formalin solution and then administered\rroutine histological follow-up series and embedded in paraffin blocks. The TUNEL method was\rused for the determination of apoptotic cells and the avidin-biotin-peroxidase complex was used for\rthe assessment of TRPM2 immunoreactivity.\rResults: MDA, apoptosis, and TRPM2 levels were increased in the I/R groups, with a significant\rincrease found in the I/R-6 group compared to the control group. Moreover, experimental ischemia-\rreperfusion cause an increase in the MDA, apoptosis, and TRPM2 levels in brain tissue.\rConclusion: TRPM2 may play a significant role in the pathophysiology of cerebral I/R injury.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Klinik Nöroloji